MicroRNA‐320c inhibits articular chondrocytes proliferation and induces apoptosis by targeting mitogen‐activated protein kinase 1 (MAPK1). (27th January 2021) - Zhao, Like; Zhou, Rongwei; Wang, Qian; Cheng, Yongjing; Gao, Ming; Huang, Cibo
Abstract: Aim: To clarify the interaction of microRNA‐320c (miR‐320c) and mitogen‐activated protein kinase 1 (MAPK1), and to investigate the effects of miR‐320c on articular chondroctye proliferation and apoptosis. Methods: Lentiviral expression vectors were constructed and dual luciferase assays containing MAPK1 3ʹ‐untranslated regions (3'‐UTRs) were performed. Small hairpin RNA (shRNA) was utilized to modulate MAPK1 expression. The messenger RNA and protein expression levels were determined by quantitative real‐time polymerase chain reaction (qRT‐PCR) and western blotting respectively. Cell Counting Kit‐8 and flow cytometry were conducted to detect the proliferation and apoptosis of Human Chondrocyte‐articular (HC‐a) cells. Besides that, the influences of miR‐320c and MAPK1 on MAPK pathway activation were also evaluated. Results: Our data identified MAPK1 as a direct target gene of miR‑320c, and miR‐320c can negatively regulate MAPK1 expression by directly binding to MAPK1 3ʹ‐UTR in HC‐a cells. Further functional study displayed that miR‐320c overexpression and MAPK1 shRNA significantly suppressed the proliferation of HC‐a cells and promoted cell apoptosis. Meanwhile, MAPK1 shRNA could attenuate miR‐320c inhibitor promotive effects on HC‐a cell proliferation and reverse its inhibitory effect on cell apoptosis. MAPK1 overexpression could rescue the inhibitory effect of miR‑320c on HC‐a cell proliferation, and weaken the accelerating effect of miR‐320c on cell apoptosis. However, neither miR‐320c or MAPK1 shRNA regulate the expression of c‐JUN, JNK and c‐Fos. Conclusion: miR‐320c inhibits articular chondrocyte proliferation and induces apoptosis by targeting MAPK1, suggesting that miR‐320c perhaps participates in the pathogenesis of osteoarthritis and acts as a potential target for the therapeutic treatment of osteoarthritis.